Second-round effects of food prices on core inflation in Turkey - Türken Fatma; Yildirim Mustafa Ozan (Economics and Business Review)
Turkey has recently experienced persistently high food inflation, among the highest in emerging markets, with food accounting for a significant proportion of consumer expenditures. This study investigates the second-round effects of food price shocks on core inflation using monthly data from January 2013 to June 2024 through a Bayesian Structural Vector Autoregressive (SBVAR) model. Incorporating domestic and international macroeconomic variables, the model identifies second-round effects by imposing theory-based constraints and leveraging Bayesian methods. Results reveal that core inflation reacts strongly to food price shocks, with rising food prices worsening inflation expectations and amplifying second-round effects on overall inflation. Historical decomposition reveals a more persistent impact of food price shocks on core inflation and expectations post-COVID-19. These findings underscore the importance of closely monitoring food price dynamics to safeguard price stability in Turkey, highlighting their critical role in shaping inflationary pressures.